KEBUTUHAN PSIKOLOGIS SISWA: PANDANGAN GURU TENTANG HAMBATAN PEMBELAJARAN BERDIFERENSIASI - Iin Karlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' educational needs encompass not only cognitive development but also psychological needs, such as motivation and optimal learning engagement. Differentiated learning is considered an approach capable of creating a conducive and inclusive learning environment. This study aims to explain teachers' perspectives on students' psychological needs in differentiated learning. The research method used in this study is a qualitative approach with a descriptive research type. Data collection techniques through interviews and documentation. Data analysis techniques in this study were carried out through the processes of data reduction, data collection, data presentation, and drawing conclusions. The results of the study indicate that fulfilling students' basic psychological needs (autonomy, competence, connectedness) requires intrinsic motivation and results in increased student confidence and comfort. However, these efforts are hampered by time constraints, the number of students, lack of teacher training, variations in student abilities, and a lack of learning resources. These obstacles make it difficult for teachers to provide individual attention, resulting in a lack of motivation, withdrawal, and lack of student initiative, thus threatening the fulfillment of psychological needs and hindering the success of differentiated learning.